The interdisciplinary nature of psychology and accounting: A review and research - Lam Khanh Tran; Hung Tri Tang; Thien Huu Nguyen (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration, 2024)
This article explores the symbiotic relationship between psychology and accounting, two social sciences investigating human behavior and decision-making. While they share common interests, methods, and challenges, the interdisciplinary nature of these fields requires careful consideration. Hence, this paper offers a comprehensive literature review, illuminating the interdisciplinary aspects of psychology and accounting and presenting a research agenda for future studies. The study adopts a qualitative approach comprising two primary phases. Firstly, a systematic literature review and content analysis are conducted to introduce the concept and dimensions of interdisciplinarity, along with its benefits and challenges. Subsequently, an in-depth analysis of the primary areas of interaction and collaboration between psychology and accounting is performed. The findings unveil current trends and challenges for psychology and accounting as social sciences, identify gaps and opportunities, and highlight the impact and implications of interdisciplinary collaboration and integration in psychology and accounting research. Furthermore, a suggested model is proposed to foster interdisciplinary.